Evaluation of night-time aerosols measurements and lunar irradiance models in the frame of the first multi-instrument nocturnal intercomparison campaign. (1st April 2019) - Barreto, A.; Román, R.; Cuevas, E.; Pérez-Ramírez, D.; Berjón, A.J.; Kouremeti, N.; Kazadzis, S.; Gröbner, J.; Mazzola, M.; Toledano, C.; Benavent-Oltra, J.A.; Doppler, L.; et al.
Abstract: The first multi-instrument nocturnal aerosol optical depth (AOD) intercomparison campaign was held at the high-mountain Izaña Observatory (Tenerife, Spain) in June 2017, involving 2-min synchronous measurements from two different types of lunar photometers (Cimel CE318-T and Moon Precision Filter Radiometer, LunarPFR) and one stellar photometer. The Robotic Lunar Observatory (ROLO) model developed by the U.S. Geological Survey (USGS) was compared with the open-access ROLO Implementation for Moon photometry Observation (RIMO) model. Results showed rather small differences at Izaña over a 2-month time period covering June and July, 2017 ( ± 0.01 in terms of AOD calculated by means of a day/night/day coherence test analysis and ± 2% in terms of lunar irradiance). The RIMO model has been used in this field campaign to retrieve AOD from lunar photometric measurements. No evidence of significant differences with the Moon's phase angle was found when comparing raw signals of the six Cimel photometers involved in this field campaign. The raw signal comparison of the participating lunar photometers (Cimel and LunarPFR) performed at coincident wavelengths showed consistent measurements and AOD differences within their combined uncertainties at 870 nm and 675 nm. Slightly larger AOD deviations were observed at 500 nm, pointing to some unexpected instrumental variations during the measurement period. Lunar irradiances retrieved using RIMO for phase angles varying between 0° and 75° (full Moon to near quarter Moon) were compared to the irradiance variations retrieved by Cimel and LunarPFR photometers. Our results showed a relative agreement within ± 3.5% between the RIMO model and the photometer-based lunar irradiances. The AOD retrieved by performing a Langley-plot calibration each night showed a remarkable agreement (better than 0.01) between the lunar photometers. However, when applying the Lunar-Langley calibration using RIMO, AOD differences of up to 0.015 (0.040 for 500 nm) were found, with differences increasing with the Moon's phase angle. These differences are thought to be partly due to the uncertainties in the irradiance models, as well as instrumental deficiencies yet to be fully understood. High AOD variability in stellar measurements was detected during the campaign. Nevertheless, the observed AOD differences in the Cimel/stellar comparison were within the expected combined uncertainties of these two photometric techniques. Our results indicate that lunar photometry is a more reliable technique, especially for low aerosol loading conditions. The uncertainty analysis performed in this paper shows that the combined standard AOD uncertainty in lunar photometry is dependent on the calibration technique (up to 0.014 for Langley-plot with illumination-based correction, 0.012–0.022 for Lunar-Langley calibration, and up to 0.1 for the Sun-Moon Gain Factor method). This analysis also corroborates that the uncertainty of the lunar irradiance model used for AOD calculation is within the 5–10% expected range. This campaign has allowed us to quantify the important technical difficulties that still exist when routinely monitoring aerosol optical properties at night-time. The small AOD differences observed between the three types of photometers involved in the campaign are only detectable under pristine sky conditions such as those found in this field campaign. Longer campaigns are necessary to understand the observed discrepancies between instruments as well as to provide more conclusive results about the uncertainty involved in the lunar irradiance models. Highlights: The first attempt to compare instruments with nocturnal remote sensing capabilities. Moon photometry has better capabilities to measure low aerosol contents. Some instrumental differences detected between the two lunar photometers. Small AOD differences only detectable in such pristine conditions were measured. A freely-available lunar irradiance model has been released.